2013
DOI: 10.1017/s0030605311001712
|View full text |Cite
|
Sign up to set email alerts
|

Population size and structure of the Nile crocodile Crocodylus niloticus in the lower Zambezi valley

Abstract: Concern has been raised about the lack of population data for the Nile crocodile Crocodylus niloticus in the lower/middle Zambezi valley. This area is important for conservation as well as being a source of crocodile eggs and adults for the ranching industry. Two spotlight surveys, in 2006 and 2009, were used to estimate population size, structure and trends. A stage-structured matrix model was parameterized from existing literature and the expected predictions were compared to those observed. The survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Despite these counterintuitive results, modeling studies and empirical data in long-lived species, such as C. acutus (Richards 2003) and sea turtles (Crouse et al 1987;Crowder et al 1994), are in agreement with our results. Models based on ages (not on stages, as in our work) applied to C. niloticus (Wallace et al 2013) and C. acutus (Briggs-Gonzalez et al 2017) showed that the annual survival of juveniles was the parameter of highest elasticity. When working with models based on stages and not ages, the estimated parameters per year should be grouped into a single population parameter according to the number of elapsed years in each stage.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Despite these counterintuitive results, modeling studies and empirical data in long-lived species, such as C. acutus (Richards 2003) and sea turtles (Crouse et al 1987;Crowder et al 1994), are in agreement with our results. Models based on ages (not on stages, as in our work) applied to C. niloticus (Wallace et al 2013) and C. acutus (Briggs-Gonzalez et al 2017) showed that the annual survival of juveniles was the parameter of highest elasticity. When working with models based on stages and not ages, the estimated parameters per year should be grouped into a single population parameter according to the number of elapsed years in each stage.…”
Section: Discussionmentioning
confidence: 47%
“…However, crocodilian populations have shown remarkable resilience if protected from overexploitation and when their wetland habitats remain intact. Remarkably, their recovery has been driven by the same commercial initiatives that caused the initial overexploitation Wallace et al 2013). Between 2011 and 2015, an average of 1.6 million crocodile and caiman skins were traded annually, all from legal, managed sources and, in many cases, based on the sustainable use of wild populations (Caldwell 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This reflects the fact that crocodiles need quiet areas. This demonstrates the positive influence of protected areas for conservation of this crocodile [32]. GLM analysis showed a correlation between different environmental factors.…”
Section: Discussionmentioning
confidence: 52%
“…The Nile crocodile is a keystone species in the Lake Kariba area and a decline in its population could result in cascading negative effects on the ecosystem (Botha et al, 2011; van der Ploeg et al, 2011; Sai et al, 2016). In addition to their ecological role, crocodiles also have economic value through ecotourism (Wallace et al, 2013); their conservation therefore benefits the local economy as well as supporting vital ecosystem functions.…”
Section: Discussionmentioning
confidence: 99%